Antineoplastic effect of compounds C14 and P8 on TNBC and radioresistant TNBC cells by stabilizing the K-Ras4BG13D/PDE6δ complex - Carrión-Estrada, Dayan A.; Aguilar-Rojas, Arturo; Huerta-Yepez, Sara; Montecillo-Aguado, Mayra; Bello, Martiniano; Rojo-Domínguez, Arturo; Arechaga-Ocampo, Elena; Briseño-Díaz, Paola; Meraz-Ríos, Marco Antonio; Thompson-Bonilla, María del Rocío; Hernández-Rivas, Rosaura; Vargas, Miguel (Frontiers in Oncology, 2024)
Introduction Breast cancer (BC) is the leading cause of cancer-related deaths among women, with triple-negative breast cancer (TNBC) representing one of the most aggressive and treatment-resistant subtypes. In this study, we aimed to evaluate the antitumor potential of C14 and P8 molecules in both TNBC and radioresistant TNBC cells. These compounds were chosen for their ability to stabilize the complex formed by the overactivated form of K-Ras4BG13D and its membrane transporter (PDE6δ). Methods The antitumor potential of C14 and P8 was assessed using TNBC cell lines, MDA-MB-231, and the radioresistant derivative MDA-MB-231RR, both carrying the K-Ras4B> G13D mutation. We investigated the compounds' effects on K-Ras signaling pathways, cell viability, and tumor growth in vivo. Results Western blotting analysis determined the negative impact of C14 and P8 on the activation of mutant K-Ras signaling pathways in MDA-MB-231 and MDA-MB-231RR cells. Proliferation assays demonstrated their efficacy as cytotoxic agents against K-RasG13D mutant cancer cells and in inducing apoptosis. Clonogenic assays proven their ability to inhibit TNBC and radioresistant TNBC cell clonogenicity. In In vivo studies, C14 and P8 inhibited tumor growth and reduced proliferation, angiogenesis, and cell cycle progression markers. Discussion These findings suggest that C14 and P8 could serve as promising adjuvant treatments for TNBC, particularly for non-responders to standard therapies. By targeting overactivated K-Ras and its membrane transporter, these compounds offer potential therapeutic benefits against TNBC, including its radioresistant form. Further research and clinical trials are warranted to validate their efficacy and safety as novel TNBC treatments.